Review of the genus Formosatettix Tinkham (Orthoptera: Tetrigidae) with description of new taxa, new synonymy and an updated key to species - Deng, Wei-An; Luo, Jie-Ling; Huang, Chao-Mei; Lin, Li-Liang (Zootaxa, 2023)
The genus Formosatettix Tinkham is reviewed. Seven new species from China, Formosatettix cliva Deng, sp. nov., Formosatettix guangyuanensis Deng, sp. nov., Formosatettix shuimogouensis Deng, sp. nov., Formosatettix strictivertex Deng, sp. nov., Formosatettix tangjiaheensis Deng, sp. nov., Formosatettix yueqingensis Deng, sp. nov., Formosatettix zheminzhengi Deng, sp. nov. are described and illustrated. One new name is proposed: Formosatettix latifemurus Deng, nom. nov. One new combination is established: Formosatettix nyalamensis (Zheng & Lin, 2015), comb. nov. The following new synonyms are established: Bolivaritettix circocephalus Zheng, 1992 = Formosatettix torulosinota Zheng & Mao, 2002, syn. nov., Criotettix bispinosus (Dalman, 1818) = Formosatettix hainanensis Zheng, 2012, syn. nov., Epitettix guangxiensis (Zheng & Jiang, 1994) = Formosatettix guangxiensis Zheng & Jiang, 1998, syn. nov., Formosatettix longwangshanensis Zheng, 1998 = Formosatettix tianmushanensis Zheng & Li, 2001, syn. nov., Formosatettix serrifemora Deng, 2019 = Formosatettix wulongensis Zha & Ding, 2020, syn. nov., Formosatettix huapingensis Zheng & Jiang, 1997 = Formosatettix nanlingensis Zheng & Cao, 2011, syn. nov. = Formosatettix undulatifemura, Zheng, 2012, syn. nov. = Formosatettix guposhanensis Deng, 2019, syn. nov. In addition, Formosatettix leigongshanensis Zha & Ding, 2020 is briefly commented.